Evaluation of Byproducts of Some Minor Millets for Chemical Composition,Mineral Profile and In Vitro Gas Production Kinetics - T.V.Girisha; V .Nagabhushana; T. Thirumalesh; K.S. Giridhar; A.M.Kotresh; R. Jayashree; N.B.Shridhar; K.C.Veeranna (Indian Journal of Animal Nutrition, 2025)
An in vitro evaluation of byproduct of selected minor millets by gas production technique followed by an in vivo evaluation of Browntop millet (Brachiariaramosa) byproduct based CFM by twelve-week feeding and metabolism trial in sheep was conducted. In vitro study revealed that ME(MJ/kg) and IVDOM(%) of Browntop (6.81 and 53.95) and Littlemillet (6.81 and 53.09) byproduct were similar whereas lower values were found in Foxtail(5.04 and 41.70), Kodomillet (5.00 and 40.26), Prosomillet (5.23 and 43.47) and poor in Barnyard (2.90 and 30.79). In vitro gas production kinetics study revealed that readily soluble fraction ‘a’ value was not detectable whereas, insoluble but fermentable fraction “b” was significantly (P<0.01) highest (34.87) in BTMBP and lowest (7.98) in BYMBP. Eighteen rams, aged 12 months (average bodyweight 26.25 kg) of non-descriptive breed were randomly allotted to three dietary treatment groups fed maize top hay based diet with wheat bran (T1) and replaced 50% (T2) and 100% (T3) wheat bran with BTMBP.The inclusion of BTMBP in either diets showed no significant difference (P>0.05) in mean DMI(83.78;82.99) as compared to T1(86.31g/kg W0.75). Intake of nutrients, except EE, were comparable. Digestibility of DM,CP,CF,NFE,NDF,ADF,C and HC was similar However, digestibility of OM and EE (P<0.05) was found high in T1 as compared to T2 and T3. Intake of TDN, DCP and ME were not influenced by the inclusion of BTMBP. The ADG (g/d) in T1(101.19), T2(91.86) and T3(88.39) were also comparable (P>0.05).It is concluded BTMBP and LTMBP were found to be nutritionally better than FXMBP,KDMBP,PSMBP. BYMBP was nutritionally poor.